SynNotch CAR-T cell, when synthetic biology and immunology meet again - Shirzadian, Mohsen; Moori, Sepideh; Rabbani, Reza; Rahbarizadeh, Fatemeh (Frontiers in Immunology, 2025)
Cancer immunotherapy has been transformed by chimeric antigen receptor (CAR) T-cell treatment, which has shown groundbreaking results in hematological malignancies. However, its application in solid tumors remains a formidable challenge due to immune evasion, tumor heterogeneity, and safety concerns arising from off-target effects. A long-standing effort in this field has been the development of synthetic receptors to create new signaling pathways and rewire immune cells for the specific targeting of cancer cells, particularly in cell-based immunotherapy. This field has undergone a paradigm shift with the introduction of synthetic Notch (synNotch) receptors, which offer a highly versatile signaling platform modeled after natural receptor-ligand interactions. By functioning as molecular logic gates, synNotch receptors enable precise, multi-antigen regulation of T-cell activation, paving the way for enhanced specificity and control. This review explores the revolutionary integration of synNotch systems with CAR T-cell therapy, emphasizing cutting-edge strategies to overcome the inherent limitations of traditional approaches. We delve into the mechanisms of synNotch receptor design, focusing on their ability to discriminate between cancerous and normal cells through spatiotemporally controlled gene expression. Additionally, we highlight recent advancements to improve therapeutic efficacy, safety, and adaptability in treating solid tumors. This study highlights the potential of synNotch-based CAR-T cells to transform the field of targeted cancer therapy by resolving present challenges and shedding light on potential future paths.